Analysis of the preoperative period and complications in valve replacement surgeries (Revista Contexto & Saúde, 2023)
Introduction: Associated with the high diagnosis of cardiovascular disease, there is a significant increase in heart surgery. Such procedures are characterized by high complexity, from which physiological changes that can lead to complications and death in the postoperative period result. Objective: To analyze clinical characteristics, risk factors, comorbidities and complications between different types of valve exchanges (TV). Method: cross -sectional, retrospective, analytical and documentary study approved by the Ethics Committee (No. 1,983,681). Included adult patients who performed elective valve exchange surgery with extracorporeal circulation, from January to December 2017 and survived. Data collection occurred from July 2018 to July 2019, in medical records of patients undergoing cardiac surgery (excluding incomplete). Results: 64 Included patients, these: 12 mitral valve exchange surgery, 32 aortic valve exchange, 2 associated mitral and aortic valve exchange, 6 valvuloplaplasties and 12 of myocardial revascularization surgery and associated valve exchange. The average and standard deviation of valve exchange surgery was: surgery time (176.72 ± 35.11min), aortic clamping time (69.16 ± 17.56 min), extra corporeal circulation time (85.47 ± 20.64 min) and ejection fraction (62.94 ± 11.28%). Statistical significance was verified in relation to the presence of systemic arterial hypertension among patients regardless of the type of TV surgery. Most (51.56%) did not have postoperative complications between surgeries. The predominant procedure was the aortic valve exchange. The type of valve exchange has not proved to be an influential factor for pre and postoperative care for this type of circus procedure. Conclusion: Patients undergoing different types of valve exchange surgeries did not differentiate the clinical profile, presence of cardiovascular risk factors, comorbidities, postoperative complications and intraoperative variables.